Orienteering and hiking programs for older adults as a model of healthy aging: a randomized clinical trial - Printes,Clarissa Biehl (2024)
OBJECTIVES: To compare the effects of orienteering vs hiking on the physical fitness and quality of life of older adults. METHODS: A 24-week randomized controlled trial was conducted with 96 participants who were assigned to orienteering (OG), hiking (HG), or a control group (CG) with no intervention. Physical fitness was assessed with the handgrip strength, chair stand, 6-minute walk, sit-and-reach, and balance tests, with monitoring of blood pressure (BP) and resting heart rate. Generalized Estimating Equations were used for within- and between-group comparisons, with effect sizes (ES) calculated. Baseline and post-intervention differences were assessed using unpaired and paired tests. RESULTS: Significant improvement in balance were observed, with OG reducing their time by -6.23 seconds (29.1%; ES = 0.83) and HG by -2.12 seconds (9.9%; ES = 0.49), p = 0.017. For paired effects, hemodynamic parameters showed a reduction in systolic (p = 0.014) and diastolic (p < 0.001) BP in the OG and in diastolic BP (p < 0.004) in the HG. Interaction effects were significant for all physical fitness and hemodynamic parameters compared with the CG (p < 0.001), with effect sizes ranging from medium to large. Quality of life significantly improved in the intervention groups (p < 0.001) compared with the CG (p = 0.571). CONCLUSION: Older adults participating in orienteering and hiking experienced improvement in their physical fitness and quality of life, with orienteering showing a greater effect on balance. These activities are valuable for healthy aging programs, as sedentary behavior should be prevented. This trial was registered at the Brazilian Clinical Trials Registry (REBEC): RBR-99jmmpf.